Development of Gluten-free Cookies Rich in Resistant Starch Type 3 from Maranta arundinacea - Nugraheni , Mutiara; Sutopo; Purwanti, Sutriyati; Widi Handayani, Titin Hera (Pakistan Journal of Nutrition, 2017)
Background and Objective: Indonesia has potential as a gluten-free food source. Thus, efforts to utilize gluten-free flour in ready-to-eat products such as cookies are required. This research aims to determine the chemical, physical and sensory characteristics of gluten-free cookies made from sorghum flour, millet flour, corn flour, tapioca flour, Maranta arundinacea flour rich in resistant starch type 3 (RS3), Maranta arundinacea flour, Coleus tuberosus flour rich in RS3 and corn starch. Materials and Methods: Four types of cookies were made, namely, wheat flour cookies (as control) and three types of gluten-free cookies based on different proportions of Maranta arundinacea flour rich in RS3 [8% (FI), 10% (FII) and 12% (FIII)]. The cookies chemical, physical and sensory characteristics were analyzed. Results: Gluten-free cookies (FI, FII and FIII) had higher contents of fibre, RS3 and calories than wheat flour cookies (as control). The physical characteristics (weight, diameter, height and spread ratio) of gluten-free cookies differed significantly from those of wheat flour cookies but did not significantly differ with the amount of added RS3. Wheat flour cookies were harder than gluten-free cookies. Wheat flour cookies had higher sensory characteristic scores (colour, flavour, taste, crispiness and overall acceptability) than did gluten-free cookies. Among the gluten-free cookies, FI had better sensory characteristic scores. Conclusion: Based on the results of this research, gluten-free cookies low in calories, rich in RS3 and high in fibre have good physical and sensory characteristics and thus can be developed as functional food.